PENGARUH MEDIA ONLINE DAN PERUBAHAN SIKAP ANAK USIA SMP (REMAJA) - Muchammad Abdul Ghofur; Dinar Primasti (REFORMASI, 2017)
Abstract: The game online is one game that is contained in the online media. In Indonesian society is not new phenomenon. Children were not spared from the 'attack' the effect of this online game play. In the middle school work pretty solid as well as a new curriculum in 2013 that made Junior High School students have an activity that is quite heavy at school, this makes the game online elementary school students are a little comforted. For this reason the researchers wanted a study that suggests the extent of exposure to the influence of online games is the changes in attitudes that occur in junior high school age children (grades 7-9) which is also known as the age of the golden age. In the implementation of this research using quantitative research methods that are supported by the questionnaire data capture technique as well as several interviews to several parties of school teachers, to seek data on how much the level of students' understanding of a given subject. Impact of online game play wish to further wants to be known by researchers as see activity at the cafe (internet cafes) in some areas in Malang there are many junior high school students. Keywords: influence of online game, online media, teens attitude change Abstrak: Permainan game online merupakan salah satu permainan yang terdapat di media online. Pada masyarakat Indonesia sudah bukanlah hal yang baru. Anak-anak pun tidak luput dari ‘serangan’ pengaruh permainan game online ini. Di tengah tugas sekolah yang cukup padat serta kurikulum baru tahun 2013 yang membuat siswa Sekolah Menengah Pertama memiliki aktivitas yang cukup berat di sekolah, game online ini membuat para siswa SMP tersebut sedikit terhibur. Untuk itulah peneliti menginginkan adanya sebuah penelitian yang mengemukakan sejauh mana pengaruh terpaan permainan game online ini terhadap perubahan sikap yang terjadi pada anak usia SMP (kelas 7-9), dimana disebut juga sebagai the golden age yaitu usia emas. Dalam pelaksanaan penelitian ini menggunakan metode penelitian kuantitatif yang didukung dengan teknik pengambilan data kuesioner serta beberapa wawancara kepada beberapa pihak dari guru sekolah, untuk mencari data seberapa jauh tingkat pemahaman siswa terhadap mata pelajaran yang diberikan. Dampak permainan game online lebih jauh ingin diketahui oleh peneliti karena melihat aktivitas pada warnet (warung internet) di beberapa wilayah di Kota Malang banyak terdapat siswa SMP. Kata Kunci: pengaruh game online, media online, perubahan sikap remaja